"How to conquer a mountain with multiple sclerosis". How a climbing expedition to Machu Picchu affects the way people with multiple sclerosis experience their body and identity: a phenomenological analysis. (18th December 2015) - Calsius, Joeri; Courtois, Imke; Feys, Peter; Van Asch, Paul; De Bie, Jozef; D'hooghe, Marie
Abstract: Background : People with multiple sclerosis (MS) frequently complain of chronic or fluctuating fatigue, sometimes accompanied by pain. From a phenomenological point of view, both fatigue and pain are seen as aspects of suffering which adversely affect the physical, psychological, social and even existential dimensions of the individual life. Objective : The present study discusses changes in identity and body awareness in people with MS who completed a 5-d trekking to Machu Picchu in Peru in 2012, after having completed a physical training schedule for several months. Method and design : All nine participants took part in a focus group organized after the trip. The Interpretative Phenomenological Analysis (IPA) was used to gain insight in their experiences and to refine pre-existing theoretical understanding of body awareness and identity. Results : Our phenomenological analysis clarified how aspects of the participants' identity and body experience before, during and after the journey influenced major daily themes as "body", "lived body", "behaviour" and "relationship" and how this contributed to a meaningful experience. When participants describe how they started looking at their own identity more consciously after being watched through the others' eyes, this resulted in a joyful transcending of their bodily power and endurance. In general, our data suggest that the more extreme, positive lived body experiences during the expedition were necessary for optimizing daily "routine" functioning. Conclusion : Participating in Machu Picchu expedition appeared to have a deep and profound effect on body awareness and identity. Participants experienced their body once again as theirs, owning it and above all, allowing it to be a source of strength, joy and meaningfulness. While MS determined their lives prior to the journey, they now could look at MS as a part of what they are, without totally being absorbed in it. So being a patient with MS before, resulted in merely having MS after the climb. Implications for Rehabilitation: Patients experience illness as a disruption of their previous life. A phenomenological approach deals with the lived experience and the concept of body awareness, the meaningful experience of living in the world through the body. This approach complements biomedical viewpoints as providing different. Suffering from a chronic and unpredictable disease like multiple sclerosis (MS) can disturb the implicit and harmonious relation between the body, the mind and the world, already at an early stage. Factors including physical training, professional guidance, social support, becoming a role model and completing a unique expedition outside of national and natural comfort borders may contribute to changes in body and identity experience.